Re-Appraisal of the Validity of Long-Run Money Neutrality: an Evidence from Nigeria: Array - Ditimi, Amassoma; Ademola, Badmus (Acta Universitatis Danubius. Œconomica, 2020)
The study re-appraised the validity of long-run money neutrality in Nigeria. The reason for this owes from the dilemma faced by monetary authorities via their inabilities to utilize an effective monetary policy that can drive and actualize her key macroeconomic objectives in a sustainable manner. The study employed Johannsen co-integration test and Vector error correction mechanism approach to re-validate the tenacity of money neutrality in Nigeria, both in the long and short-run using annual time series data from 1981 to 2018. The results from the Phillips curve model refutes the validity of longrun money neutrality while that of Fishers effect relation exerted partial long-run money neutrality in Nigeria. Hence, revealing that Fishers effect is more effective in validating money neutrality in Nigeria comparatively. Similarly, the Normalized co-integration test and the VECM estimate, supported that of the above. Also, the error correction model (ECM) suggest that, for money to be wholly neutral in the long-run, it will take one year and nine months. Consequently, the study concludes that the old debate of money neutrality is not entirely practicable in Nigeria due to the existence of nominal rigidity and partial violation of the classical and monetarist dichotomies of monetary aggregates. Based on the above conclusion, the study recommends that the government should adopt sound policy coordination to achieve an overall macroeconomic objective in the long-run. Furthermore, the CBN should put all measures in place to suppress the uncomplimentary time lag between the time they spot the need for changes in monetary policy and the time to take action, to enhance a successful result of fine-tuning monetary policy instruments.